Stem cell-derived extracellular vesicles mitigate ageing-associated arterial stiffness and hypertension. Issue 1 (1st January 2020) - Feng, Rui; Ullah, Mujib; Chen, Kai; Ali, Quaisar; Lin, Yi; Sun, Zhongjie
ABSTRACT: The prevalence of arterial stiffness and hypertension increases with age. This study investigates the effect of induced pluripotent mesenchymal stem cell-derived extracellular vesicles (EVs) on ageing-associated arterial stiffness and hypertension. EVs were collected and purified from induced pluripotent stem cell-derived mesenchymal stem cells (iPS-MSCs). Young and old male C57BL/6 mice were used. Mice in the EVs group were injected via tail vein once a week for four weeks (18 x 10 6 EVs/mouse/injection). Blood pressure (BP) was measured using the tail-cuff method and validated by direct cannulation. Pulse wave velocity (PWV) was measured using a Doppler workstation. PWV and BP were increased significantly in the old mice, indicating arterial stiffness and hypertension. Intravenous administration of EVs significantly attenuated ageing-related arterial stiffness and hypertension, while enhancing endothelium-dependent vascular relaxation and arterial compliance in the old EVs mice. Elastin degradation and collagen I deposition (fibrosis) were increased in aortas of the old mice, but EVs substantially improved ageing-associated structural remodelling. Mechanistically, EVs abolished downregulation of sirtuin type 1 (SIRT1), and endothelial nitric oxide synthase (eNOS) protein expression in aortas of the older mice. In cultured human aortic endothelial cells, EVs promoted the expression of SIRT1, AMP-activated protein kinase alpha (AMPKα), and eNOS. In conclusion, iPS-MSC-derived EVs attenuated ageing-associated vascular endothelial dysfunction, arterial stiffness, and hypertension, likely via activation of the SIRT1-AMPKα-eNOS pathway and inhibition of MMPs and elastase. Thus, EVs mitigate arterial ageing. This finding also sheds light into the therapeutic potential of EVs for ageing-related vascular diseases. Abbreviations: EV: Extracellular vesicles; iPS: induced pluripotent stem cell; MSC: mesenchymal stem cell; AMPKα: AMP activated protein kinase α; eNOS: endothelial nitric oxide synthase; Sirt1: sirtuin 1; JNC7: Seventh Report of the Joint National Committee; CVD: cardiovascular disease; PWV: pulse wave velocity; BP: blood pressure; SNP: sodium nitroprusside